Artifical intelligence and international security: the upcoming revolution in military affaris - Kopanja, Mihajlo (Sociološki pregled, 2023)
In the existing literature it is possible to find more and more research making a connection between artificial intelligence and international security. It is understandable having in mind that the development trends of modular and general artificial intelligence and their implementation in the domain of security threaten to lead to radical transformation of the manner in which military affairs are conducted. The research aim of this paper is to provide a review of the existing research that makes a connection between artificial intelligence and international security for the purpose of confirming the hypothesis that development and implementation of artificial intelligence announce the upcoming revolution in military affairs, which will transform the manners of the states’ entering strategic interactions and mutually realizing them.